A zona de convergência do atlântico sul e sua relação com a oscilação Antártica - Rosso, Flávia Venturini (2017)
During the rainy season (october-march) over the southeast of Brazil there is a band of convective nebulosity that extends generally from the south of the Amazon to the southwest Atlantic ocean, known as the South Atlantic Convergence Zone (SACZ). It is of great interest because it generates high accumulations of rain in the regions where it operates, causing serious damage to society. The SACZ is influenced by atmospheric variability at various time scales, but few studies explore the influence of extratropical circulation on its formation. Therefore, the objective of this work is to evaluate the role of the Antarctic oscillation (AAO) phases in the events of SACZ. For this, cases of SACZ events were selected from 1992 to 2015, daily precipitation data from 1980 to 2013, ERA-INTERIM daily data (air temperature, dew point temperature, geopotential height at 200 hPa and 700 hPa, sea level pressure, zonal wind at 200 hPa and 850 hPa and meridional wind at 850 hPa components) for the period 1980 to 2015 and daily outgoing long-wave radiation (OLR) data obtained from the National Oceanic and Atmospheric Administration (NOAA) between 1974-2013. The reanalysis and OLR data were filtered in the intrasazonal band (10-100 days) and after the fields of the lagged composition of each variable were created for each phase of the AAO. The initial results, using statistical analysis, showed that both the persistence and frequency of SACZ events are greater in AAO+. The sign of precipitation over the climatological region of the SACZ was evident in both phases, but especially in the AAO+, which showed the highest values accumulated per event. The lagged fields of the daily precipitation anomalies were generated and in general, in both phases of the AAO, from lag 1 there is an extensive area of positive anomalies in the SACZ region, weakening from the lag 6. It is also noticeable that from the lag 0 negative precipitation anomalies of the south of Brazil appear, which weaken from lag 7, in the two phases of AAO. The composites of the intrasonal anomalies of the variables used coherently represented the circulation patterns associated with the occurrence of the SACZ, with the strongest and most comprehensive signs from the lag 0 (day of onset of the event), in both phases of the AAO. It can be concluded, then, that the signal of the influence of the AAO phases on the SACZ events is best represented in the precipitation field, and during the AAO+ the events were more frequent and persistent, presenting the highest accumulations of rainfall.